Extraction of Copper, Cobalt and Nickel by Leaching of Iron (III) Sulfate from Copper Slags - Arslanoglu, Hasan; Altundogan, H. Soner; Tumen, Fikret (Springer India, 2022)
In this study, the recovery of copper, cobalt and nickel by oxidizing leaching using iron (III) sulfate from reverber and converter slags obtained from Ergani Bakir businesses in the period of operation was investigated. The effects of temperature, time, amount of iron (III) sulfate and solution/slag ratio on the solution of metals were investigated. It was determined that the metals from the reverber slag could not be taken into solution at a satisfactory rate. It has been determined that about 94% of copper (Cu(II)) can be taken into solution from converter slag, while about 40-50% of cobalt (Co(II)) and nickel (Ni(II)) can be extracted.
Keywords: Copper slags; Metal recovery; Cu-Co-Ni; Iron (III) sulfate; Leaching